The Impact of Design-Based Research Method Science Activities on Middle School Students' Creative and Critical Thinking Skills: A Classroom Experimental Study - Yılmaz, Adem (Kastamonu Egitim Dergisi, 2025)
Purpose: The purpose of this study is to investigate the effect of science activities prepared through the design-based research (DBR) method on middle school students' creative and critical thinking skills. Design/Methodology/Approach: A quasi-experimental design was employed. The study group consisted of 80 middle school students in Kastamonu, Turkey, randomly assigned to experimental and control groups. Design-based science activities were applied in the experimental group, while the control group followed traditional science instruction. Data were collected through pre-tests and post-tests using the Marmara Creative Thinking Dispositions Scale and Marmara Critical Thinking Dispositions Scale. Findings: Results indicated significant improvements in creative and critical thinking dispositions of students in the experimental group compared to the control group. The DBR activities provided students with active problem-solving opportunities, enhancing their ability to generate creative ideas and critically evaluate their work. Highlights: The study highlights that the design-based research approach in science education is more effective than traditional teaching methods in enhancing creative and critical thinking skills. It is recommended for educators and curriculum developers to integrate DBR-driven activities into educational programs.